2016
DOI: 10.1242/bio.017442
|View full text |Cite
|
Sign up to set email alerts
|

Caenorhabditis elegansglutamylating enzymes function redundantly in male mating

Abstract: Microtubule glutamylation is an important modulator of microtubule function and has been implicated in the regulation of centriole stability, neuronal outgrowth and cilia motility. Glutamylation of the microtubules is catalyzed by a family of tubulin tyrosine ligase-like (TTLL) enzymes. Analysis of individual TTLL enzymes has led to an understanding of their specific functions, but how activities of the TTLL enzymes are coordinated to spatially and temporally regulate glutamylation remains relatively unexplore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…The C . elegans genome encodes five TTLL glutamylases— ttll-4 , ttll-5 , ttll-9 , ttll-11 , and ttll-15 [ 6 , 28 ]. We previously showed that ttll-4 mutation suppresses the ccpp-1 Dyf defect, suggesting that TTLL-4 glutamylates microtubules in amphid and phasmid cilia [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The C . elegans genome encodes five TTLL glutamylases— ttll-4 , ttll-5 , ttll-9 , ttll-11 , and ttll-15 [ 6 , 28 ]. We previously showed that ttll-4 mutation suppresses the ccpp-1 Dyf defect, suggesting that TTLL-4 glutamylates microtubules in amphid and phasmid cilia [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The avoidance behaviour towards high osmolality is one of the best-characterised sensory behaviours of C. elegans 27 . Since ttll-4 -deficient worms showed subtle defects of avoidance behaviour towards high osmolality 28 , the assay was sensitized using as low as 2 M NaCl solutions (Supplementary Fig. S9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, three strategies are used to study tubulin glutamylation: (1) genetic perturbation of genes that encode glutamylation-modifying enzymes, (2) manipulation of the glutamylation levels of purified microtubules by recombinant enzymes in vitro , and (3) introduction of specific antibodies to mask the glutamylated motifs of microtubules. Although all of the above experiments imply that glutamylation is important for the structural integrity and functions of cilia ( Gaertig and Wloga, 2008 ; Konno et al, 2012 ; Grau et al, 2013 ; Pathak et al, 2014 ; Chawla et al, 2016 ), these conventional methods have several limitations.…”
Section: New Methods Enabling the Spatiotemporal Manipulation Of Axonmentioning
confidence: 99%
“…Moreover, the localization of TTLL7 in cilia of transfected MDCK cells also implies that it has a role in ciliary glutamylation, although more studies are required to confirm this (Van Dijk et al, 2007). Janke et al, 2005;Van Dijk et al, 2007;Wloga et al, 2008;Vogel et al, 2010;Pathak et al, 2011;Ye et al, 2018;Lan et al, Van Dijk et al, 2007;Kashiwaya et al, 2010;Kimura et al, 2010;Lacroix et al, 2010;Rogowski et al, 2010;O'Hagan et al, 2011;Pathak et al, 2011;Ye et al, 2014;Casanova et al, 2015;Chawla et al, 2016;Ijaz et al, 2017;Kimura et al, 2018;Ye et al, 2018;Mahalingan et al,…”
Section: Modulation Of Glutamylation On Ciliary Axonemes Tubulin Glutmentioning
confidence: 99%